The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.7759/cureus.2236
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported Outcome Measurements on the Tolerance of Magnetic Resonance Imaging-guided Radiation Therapy

Abstract: PurposeMagnetic resonance imaging-guided radiation therapy (MRgRT) requires patient positioning within the MR bore and prolonged MR imaging during delivery, both of which are new in radiation oncology. Patient tolerance of MRgRT was prospectively evaluated using patient-reported outcome questionnaires (PRO-Q).MethodsOur MRgRT procedure involves daily high-resolution MR scanning, limited re-contouring, daily plan re-optimization, quality assurance (QA), and gated delivery. Patients with claustrophobia are exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
40
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 7 publications
8
40
0
Order By: Relevance
“…In our cohort, all fractions could be administered safely, without patient-induced early terminations, and, as expected, without any treatment-related severe toxicities. The PRO-Q results shown in this manuscript confirm that treatment at the MR-Linac is generally well tolerated by patients, which is in accordance with results previously published by Tetar et al [26]. Compared to their rate of MR-related patient complaints of 29%, the value of 65% in our study is considerably higher, while, on the other hand, none of our patients reported considerable anxiety.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our cohort, all fractions could be administered safely, without patient-induced early terminations, and, as expected, without any treatment-related severe toxicities. The PRO-Q results shown in this manuscript confirm that treatment at the MR-Linac is generally well tolerated by patients, which is in accordance with results previously published by Tetar et al [26]. Compared to their rate of MR-related patient complaints of 29%, the value of 65% in our study is considerably higher, while, on the other hand, none of our patients reported considerable anxiety.…”
Section: Discussionsupporting
confidence: 93%
“…We have shown that MR-guided respiratory gating in breath-hold is feasible and, combined with a real-time au-diovisual feedback system, was very well tolerated and appreciated by patients. This confirms the positive results of Tetar et al [26]. Cine-MR-enabled gating in breath-hold is also effective; we observed a mean gating duty cycle of 72%, similar to the range of 67% to 87% published by van Sörnsen de Koste et al [17] using a predecessor of the MRIdian Linac system [12].…”
Section: Discussionsupporting
confidence: 91%
“…Video feedback for breath-hold delivery has been positively viewed by patients treated on the MR-linac. 9 Commonly no immobilization is necessary, with the patient arranged comfortably on the couch. No implanted fiducials are required either, making for a safer and noninvasive treatment.…”
Section: A | Dr Andrew Godleymentioning
confidence: 99%
“…There is limited literature available to describe patients’ experience of BH. A recent study evaluated 150 patients’ experiences of voluntary BH using MR-guided RT using an un-validated questionnaire [ 11 ]. Considerable difficulty controlling their tumor position in voluntary BH was reported by 12.5% of patients [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study evaluated 150 patients’ experiences of voluntary BH using MR-guided RT using an un-validated questionnaire [ 11 ]. Considerable difficulty controlling their tumor position in voluntary BH was reported by 12.5% of patients [ 11 ]. Another study investigated the patient experience of DIBH, in 41 patients receiving breast RT [ 12 ].…”
Section: Introductionmentioning
confidence: 99%